(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In today’s educational environment, where innovative teaching methods and approaches are increasingly valued, it is important to cultivate visual and creative competencies in teachers. This article explores the theoretical foundations necessary to enhance the visual and creative abilities of future teachers. Drawing on theories from psychology, education, and cognitive science, this article explores the importance of visual and creative abilities in developing effective teaching practices. By integrating theoretical foundations such as constructivism, multiple intelligences, and creative thinking models, teachers can be equipped with the necessary tools to engage and inspire students in a variety of learning environments.